THE URGENCY OF REGULATING SEXUAL GRATIFICATION AND SEXTORTION AS PATHOLOGICAL BEHAVIOR OF BUREAUCRATS - Amalia Syauket; Tri Endah Karya Lestiyani; Ketut Adi Wirawan (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Extortion, gratuities and bribery are the most common acts of corruption and are prone to involving bureaucrats, will harm the state and as crimes threaten the norms, values ​​and integrity of the nation. The bureaucracy has a mode of corruption in the form of gratification, then sex gratification appears which gets the public's attention. Sextortion is a form of sexual extortion related to abuse of power. Sex gratification and sextortion are pathologies of bureaucrat behavior related to corrupt behavior, manifested in negative or dysfunctional behavior. There is a high urgency for regulation of sex gratification and sextortion in explicit regulations because of the urgent need for legal certainty and easier proof to be carried out by the KPK. Article 12B of Law Number 20 of 2001 does not contain the word gratification in the form of sex services. This means that there are no regulations or laws stating that the act of providing sexual services (sex gratification) is an act of corruption. Likewise, the absence of laws targeting sextortion as a form of corruption causes it to become a form of covert corruption. The novelty of the research is that sex gratification and sextortion are icebergs as a result of a void in norms, difficult to be charged with criminal law, difficult to prove and weak sanctions do not create a deterrent effect.